Evaluation of Serum Ferritin in Diffuse Hair Loss Among Females - Hana Hafalish; Suad Altubouli (AlQalam Journal of Medical and Applied Sciences, 2025)
Since iron is necessary for vital function in the hair follicle, iron deficiency may interfere with the production of new hair. The connection between levels of body iron and loss of hair has been looked at by numerous studies, but in terms of the results, they have been largely inconsistent. The study aimed to determine if lower stores of tissue iron, as demonstrated by blood ferritin levels, are evident in patients with female pattern hair loss and chronic telogen effluvium. The study was carried out in our dermatology clinic and was cross-sectional. 50 patients diagnosed with hair loss of chronic diffuse type, aged 18 to 60, were enlisted. Only 2% of cases had serum ferritin levels within the recommended level. Although low serum ferritin is frequent in women, our research showed no discernible link between it and diffuse hair loss.